(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This bibliometric analysis explores weight-bearing exercise research in sports science from 1997 to 2022. We began with 729 documents, refining to 49 open access articles. Findings reveal a modest decline in research output, emphasizing the need for renewed interest. However, a high average citation rate (44.02) indicates the impact of existing research. Global collaboration, with a 30.61% international co-authorship rate, enriches the field. Diverse keywords reflect multifaceted research. Annual production analysis shows evolving trends, from early interest to recent fluctuations. The United States leads in scientific production, underlining the global nature of weight-bearing exercise research. This analysis informs future research priorities in sports science.